KARAKTERISTIK CAMPURAN ASPAL BETON AC-WC DENGAN SUBSTITUSI BUTON ROCK ASPHALT TERHADAP RENDAMAN AIR BERLUMPUR - Asrol Asrol; Sofyan M. Saleh; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Puddle is one of the damaging effects that can reduce the quality of pavement. The quality of road construction with asphalt pavement is determined by its stability, flexibility, and durability which are the determinants of the quality of pavement. In this research, Buton Rock Asphalt (BRA) was used as an alternative to improve the performance of asphalt mixture that can be impacted by the mentioned determinants. BRA is Asphalt Buton type 5/20 grain Asbuton type which has penetration value 5 mm and bitumen content of 20%. The aim of this research was to measure the best percentage of BRA level from percentage of BRA substitution (25%, 50%, 75%, 100%) as filler and Marshall mix parameter value of Pen 60/70 asphalt with the best BRA Substitution on immersion water with variation of immersion time 30 minutes, 24 hours. Based on Marshall test result with BRA substitution, percentage variation obtained the best stability at 50%, BRA percentage was 1450,78 kg, density 2,45 gr / cm3, VIM equal to 4,17%, VMA equal to 21,76%, VFA equal to 80, 86% and 2.5 mm of flow, and Marshall Quentient of 583.40 kg / mm. This suggested that the use of BRA as a filler substitute material at 50% percentage was the best percentage of BRA substitution with the highest stability value and it met the requirements of other Marshall parameters. The best stability value without substitution with a muddy water bath was 1098.95 kg, with the best BRA substitution of 1476.34 kg. This indicated that the use of BRA as a filler substitute material had an effect on increasing the stability value of AC-WC asphalt mixture to muddy water immersion.